PENERAPAN GERAKAN SERIBU BIOPORI (GASEBO) DALAM MENGATASI PROBLEMATIKA SAMPAH ORGANIK - Yuliani, C.; Kusuma, M.R.; Pastika, I.P.; Wisudawati, N.N.S. (Buletin Udayana Mengabdi; Vol 20 No 2 (2021): Buletin Udayana Mengabdi, 2021)
This study aims to solve the problem related to waste in Penebel Village and make Penebel Village an Environment-Based Tourism Village. The scope of this research is the understanding of biopori, the advantages and benefits of making biopori holes, how to make biopori, and biopori sustainable plans in Penebel Village. The method used is direct observation and practice of how to make biopori holes. The results of the implementation of biopori are expected to overcome the problem of waste and show that Penebel Village is used as a place of research as well as a pioneer in the application of biopori, which later if it continues to be applied it will produce better benefits for Penebel Village. In realizing sustainable community empowerment, in accordance with the desired vision so that Penebel Village is free from waste, a sustainable plan is planned, that is, each community can sort organic and non-organic waste. Where organic waste can be put into a biopori hole and the results after it decomposes it can be used as compost. For maximum results in reducing household waste in each home it is expected to have a minimum of 10 biopori holes.